2017
DOI: 10.5194/gmd-10-3225-2017
|View full text |Cite
|
Sign up to set email alerts
|

JRAero: the Japanese Reanalysis for Aerosol v1.0

Abstract: Abstract. A global aerosol reanalysis product named the Japanese Reanalysis for Aerosol (JRAero) was constructed by the Meteorological Research Institute (MRI) of the Japan Meteorological Agency. The reanalysis employs a global aerosol transport model developed by MRI and a twodimensional variational data assimilation method. It assimilates maps of aerosol optical depth (AOD) from MODIS onboard the Terra and Aqua satellites every 6 h and has a TL159 horizontal resolution (approximately 1.1 • × 1.1 • ). This pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 107 publications
(139 reference statements)
1
73
0
Order By: Relevance
“…Apart from being a potent assimilation tool it is shown here that LIVAS constitutes an ideal observational dataset for the evaluation of climate model simulations and reanalysis datasets, and the need for more studies towards this direction is acknowledged. It is suggested that dust products from more recent reanalysis projects such as the CAMS interim reanalysis (CAMSiRA) (Flemming et al, 2017), the Modern-Era Retrospective analysis for Research and Applications, Version 2 (MERRA-2) (Gelaro et al, 2017) and the Japanese Reanalysis for Aerosol (JRAero) (Yumimoto et al, 2017) should be evaluated in a similar way (2-D or 3-D evaluation depending on the availability of dust profile data).…”
Section: Seasonal Biases Between Macc and Livas Dust Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from being a potent assimilation tool it is shown here that LIVAS constitutes an ideal observational dataset for the evaluation of climate model simulations and reanalysis datasets, and the need for more studies towards this direction is acknowledged. It is suggested that dust products from more recent reanalysis projects such as the CAMS interim reanalysis (CAMSiRA) (Flemming et al, 2017), the Modern-Era Retrospective analysis for Research and Applications, Version 2 (MERRA-2) (Gelaro et al, 2017) and the Japanese Reanalysis for Aerosol (JRAero) (Yumimoto et al, 2017) should be evaluated in a similar way (2-D or 3-D evaluation depending on the availability of dust profile data).…”
Section: Seasonal Biases Between Macc and Livas Dust Profilesmentioning
confidence: 99%
“…The amount of dust emitted into the atmosphere depends on surface wind speed and on factors such as soil texture, soil moisture and vegetation cover (IPCC, 2013). Dust is also produced locally from anthropogenic activities (e.g., manufacturing, construction, mining, agricultural activities, herding livestock, off-road vehicles and warfare) (Zender et al, 2004). On a global scale, it has been estimated that natural sources account for ∼ 75 % and anthropogenic sources for ∼ 25 % of the dust emissions (Ginoux et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Model difficulties in reproducing these atmospheric dust properties are largely associated with their inability to accurately simulate important dust processes, such as dust emission, transport, and deposition (e.g. Ginoux et al, 2001;Shao, 2001;Zender et al, 2003;Huneeus et al, 2011;Kok et al, 2017). Dust aerosols are emitted from source regions such as the Saharan, Middle East, and Asian deserts and are deposited after they are transported for thousands of kilometres (Duce et al, 1980;Prospero et al, 1981;Weinzierl et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, assimilation of AOD and aerosol observations are required to further improve the representation of primary aerosol emissions and concentrations (e.g. Yumimoto et al, 2017). Simultaneous assimilation of trace gas and aerosol observations would be a powerful approach to fully represent aerosol-gas interactions in the data assimilation framework, which would improve both trace gas and aerosol data assimilation analysis.…”
Section: Aerosolsmentioning
confidence: 99%